Simulation of AI based PSO algorithm in WSN - Herakal, Renuka C; Talanki, Suresha (International Journal of Engineering and Technology, 2019)
In the evolving technologies, the Wireless Sensor Network (WSN) has perceived tremendous influences in the past two decades for rectifying the problems of energy immorality to certify the rate of energy consumption of nodes in dynamic deployment and the average computation time. It has been analyzed that, the Particle Swarm Optimization (PSO) algorithm is deliberated as one of the best suited algorithms for Dynamic Deployment of nodes in WSN. It is also examined that, the PSO algorithm doesnâ€™t have dynamic support in sustaining the rate of energy consumption limit and moderate computation time. Hence, this work presents a novel idea where the rate of energy consumption in dynamic deployment of nodes and average computation time of information is reduced by applying the Artificial Intelligence (AI) technique to the existing PSO algorithm. This paper also discusses the complete algorithm and its architecture based on AI.Â Â Â